Gross Anatomy of the Female Reproductive System of Sugar Gliders (Petaurus breviceps) - María del Mar Yllera; Diana Alonso-Peñarando; Matilde Lombardero (Animals, 2023)
We dissected carcasses of eight mature females, both parous and non-parous specimens, to study the macroscopic anatomy of the female reproductive system in the sugar glider. The genital system includes double organs, namely the right and left ones, which are completely separated. It includes two ovaries, two oviducts, two uteri and a vaginal complex. The uteri are fusiform-shaped and lack horns. The vaginal complex includes two lateral vaginae and a median vagina, also called the ‘birth canal’. The cranial end of both lateral vaginae partially fuses, forming an expansion named the vaginal sinus, which is divided into two parts by a longitudinal septum, one for each vagina, where the ipsilateral uterine cervix opens. The caudal end of the lateral vaginae opens into a medial and impar duct: the urogenital sinus that serves as a common passage for the reproductive and urinary systems. In non-pregnant females, only the lateral vaginae are present. In pregnant and recently parous females, a short median vagina extends from the caudal wall of the vaginal sinus to the cranial end of the urogenital sinus. In the ventral wall of this sinus, next to its caudal opening, there is a forked clitoris.